If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -1(u + -9) + 1 = 4 Reorder the terms: -1(-9 + u) + 1 = 4 (-9 * -1 + u * -1) + 1 = 4 (9 + -1u) + 1 = 4 Reorder the terms: 9 + 1 + -1u = 4 Combine like terms: 9 + 1 = 10 10 + -1u = 4 Solving 10 + -1u = 4 Solving for variable 'u'. Move all terms containing u to the left, all other terms to the right. Add '-10' to each side of the equation. 10 + -10 + -1u = 4 + -10 Combine like terms: 10 + -10 = 0 0 + -1u = 4 + -10 -1u = 4 + -10 Combine like terms: 4 + -10 = -6 -1u = -6 Divide each side by '-1'. u = 6 Simplifying u = 6
| a-0.13=0.58 | | 11x-16=270 | | 5+4X=X+8 | | 14a+(-93)=49+(-57a) | | 9x+12=192 | | 10-5x=-14+(4-x) | | 5*8x= | | -8=-2-x/2 | | 8x-3=141 | | -16x-(-18)= | | 7x-12x+7= | | 7x+43=386 | | x-5+9x=2x-6+5 | | 11m+5n-2m+9n= | | 6x-31=77 | | 7x-7=12-(5x+7) | | 84=5m+3(4m-6) | | 3x+8=11+2x | | 314=13(x-2)-(12x-13)+2(150+x) | | 8t-2=16(t-2.5) | | 2+2y=-6 | | 4x+3=12x-13 | | 1+3x=16-2r | | 6+9x=8x-12 | | 12h=10h | | 3-4x=44 | | 56x+2=42x+5 | | 5-8x=24 | | 4x-25=105 | | 5x-9=13x-(8x-4) | | 2x-4-5x+10=40 | | 3x+17=59 |